Mission Unaccounted: Japan's Shift of Role in US Extended Nuclear Deterrence - Kawai, Kimiaki (Journal for peace and nuclear disarmament, 2022)
Japan's security policy appears to be undergoing a qualitative change. Policymakers, however, have not provided sufficient explanation to the nation regarding such a shift. What is the qualitative change in Japan's security policy premised on US extended nuclear deterrence? To answer this question, this article first analyzes changes both in Japanese policymakers' understanding of US extended nuclear deterrence and the concept of nuclear deterrence, and the shift of Japan's defense policies. Next, a comparison of deliberations in the National Diet of Japan during the Cold War and after the Cold War, and Japan's defense policies during the Cold War and after the Cold War, respectively, reveals that while policymakers' understanding of US extended nuclear deterrence and the concept of nuclear deterrence have not really changed, the security challenges surrounding Japan have shifted in focus from deterrence to response in the recognition of policymakers. With that, Japan's policy premised on US extended nuclear deterrence has shifted from the stage of mere reliance to the stage of engagement with the United States. This is the qualitative change in Japan's security policy premised on US extended nuclear deterrence. The implication of the shift is that the use of nuclear weapons itself is a potential policy issue, yet it remains unexamined. The final section points out that Japan's engagement with the United States in extended nuclear deterrence advances the move toward solidification of US extended nuclear deterrence for Japan. It also discusses Japan's security challenges associated with the ongoing solidification.